PRE-SERVICE ELEMENTARY MATHEMATICS TEACHERS' VIEWS ON GEOMETRIC CONSTRUCTIONS: BUILDING ON THE PAPER OR INTERACTIVE WHITEBOARD? - Meral CANSIZ AKTAŞ; Hayal YAVUZ MUMCU (Informascope, 2019)
This study examined pre-service teachers' views and experiences of building geometric constructions on paper and with the interactive whiteboard. The study group consisted of 26 pre-service elementary teachers in a state university in the Black Sea region of Turkey who took the Geometry Teaching course. The data were obtained from an opinion form consisting of open-ended questions and field notes. Findings revealed that almost all of the teachers had no experience with geometric constructions in their previous education and the majority of pre-service teachers' opinions about geometric construction activities are positive. They experienced more problems when building geometric constructions on the interactive whiteboard so their opinions about building geometric constructions on paper are more positive than building on the interactive whiteboard. Moreover, it was determined that pre-service teachers' views imply that building geometric constructions on the interactive whiteboard makes sense in the affective learning domain, whereas building on paper contributes more to the cognitive learning domain.